Hysterectomy for the Management of Menstrual Hygiene in Women With Intellectual Disability. A Systematic Review Focusing on Standards and Ethical Considerations for Developing Countries - Márquez-González, Horacio; Valdez-Martinez, Edith; Bedolla, Miguel (Frontiers in Public Health, 2018)
Abstract Background: Menstruation is considered problematic for women with intellectual disability (ID). In low-and middle-income countries, where these women do not have access to facilities and resources for adequate menstrual care, hysterectomy may be seen as a morally acceptable procedure. We conducted the first systematic review to determine what constitutes best practice for menstrual hygiene in women with intellectual disability (ID) as a context to explore the perspectives of actors involved in the hysterectomy decision. Methods: Theory-informed mixed-method thematic systematic review with theory development. Results: Eleven ethical guidelines and 17 studies were included. Respect for autonomy and the patient’s best interest were the criteria to determine what constitutes best practice. The actors’ values and attitudes expressed some dimensions of existing inequities. The main parents’ concerns included difficulty teaching their daughters menstrual hygiene and the limited support networks; for women with ID, menstruation was a negative experience. Hence, both parties supported hysterectomy for menstrual hygiene. Doctors perceived hysterectomy as a safe procedure and a solution for women whose menstrual hygiene is problematic. The more severe or profound the level of ID, the more likely the interested parties advocated for a hysterectomy, mainly in low-and middle-income countries. Parents and doctors considered informed consent or assent (from the women with ID) just as something that can be achieved or conceded. Conclusion: There is an urgent need for ethics based political reform to improve health policies and programs targeted at women with ID over the issue of hysterectomy and menstrual care. Keywords: intellectual disability, hysterectomy, menstruation, hygiene, developing countries.